Gestión de riesgo cambiario: clave en la planeación financiera de una compañía exportadora (2013)
This document deals descriptively with the management of foreign exchange risk and how it should be geared to corporate financial planning through tools such as financial hedges, which are essential for mitigating this risk in exporting companies. This study considers that the joint implementation of these tools will result in the type of coverage indicated, which will provide flexibility in decision making and contribute -if the market allows it- to the generation of value for the company and its shareholders.